The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1172/jci.insight.145470
|View full text |Cite
|
Sign up to set email alerts
|

Sodium in the dermis colocates to glycosaminoglycan scaffold, with diminishment in type 2 diabetes mellitus

Abstract: Background: Dietary sodium intake mismatches urinary sodium excretion over prolonged periods. Our aims were to localize and quantify electrostatically bound sodium within human skin using triple quantum filtered (TQF) protocols for magnetic resonance imaging (MRI) and spectroscopy (MRS), and explore dermal sodium in Type 2 Diabetes Mellitus (T2D). Methods:We recruited adult participants with T2D (n=9) and euglycemic participants with no history of Diabetes Mellitus (n=8). All had undergone lower limb amputatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Here, Na + bound possibly colocalizes with the glycosaminoglycan scaffold as demonstrated in humans [52] and rodents [53]. The responses of Na + balance to the treatments by Losartan and Ang- (3)(4) in CTRL and RBD rats-especially the accentuated negative Na + balance with the combined treatment-lead us to conclude that they rely on the inhibition of the Ang II)AT 1 R axis and the counteracting stimulation by Ang-(3-4) of the Ang II)AT 2 R axis [12].…”
Section: Plos Onementioning
confidence: 69%
“…Here, Na + bound possibly colocalizes with the glycosaminoglycan scaffold as demonstrated in humans [52] and rodents [53]. The responses of Na + balance to the treatments by Losartan and Ang- (3)(4) in CTRL and RBD rats-especially the accentuated negative Na + balance with the combined treatment-lead us to conclude that they rely on the inhibition of the Ang II)AT 1 R axis and the counteracting stimulation by Ang-(3-4) of the Ang II)AT 2 R axis [12].…”
Section: Plos Onementioning
confidence: 69%
“…It has been thought that hyperglycemia and the associated diuresis, glucosuria, and hyperinsulinemia cause upregulation of renal glucose transporters and sodium channels, leading to increased renal sodium reabsorption 64 , 65 . On the other hand, recent studies using 23 Na magnetic resonance imaging have reported that sodium can be stored in the skin in an osmotically inactive form and that this dermal Na-binding capacity is reduced in T2D patients 60 , 66 . Our results indicate that in dialysis patients who have already lost renal function, diabetic patients are still more impaired in sodium regulation than non-diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Ideal phantoms for standard 2D-FT-MRI should exhibit therefore a strong anisotropy with regard to in-plane lateral distance of the grid bars with reference to their structural height in slice (z-) direction. Usual slice thickness in 2D-FT-microscopy ranges between 50 and 200 μm (see, e.g., [9,12,26]). The demands on the manufacturing technology for offering lateral structures down to 1 μm at height of 50-200 μm, corresponding to aspect ratios of about 50-200 are therefore very challenging.…”
Section: Methods For Proving Spatial Resolution In Mri: Actual Statementioning
confidence: 99%
“…MRI with pixel size in that spatial range is therefore called MR-microscopy (MRM) [5]. MR-based histology [6] in the microscopic range has been reported on pathologic structural changes in tissue samples ex-vivo, for arteriosclerosis [7], arthritic changes in cartilage [8], diabetes related changes in the human skin [9] and ovarian cancer [10].…”
Section: Advances In High Resolution Mri Based Medical Imagingmentioning
confidence: 99%